2014
DOI: 10.1037/a0035667
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic assessment promotes treatment readiness but does not affect symptom change in patients with personality disorders: Findings from a randomized clinical trial.

Abstract: The field of clinical personality assessment is lacking in published empirical evidence regarding its treatment and clinical utility. This article reports on a randomized controlled clinical trial (N = 74) allocating patients awaiting treatment in a specialized clinic for personality disorders to either 4 sessions of (a) therapeutic assessment (TA) or (b) a structured goal-focused pretreatment intervention (GFPTI). In terms of short-term outcome, TA demonstrated superior ability to raise outcome expectancies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 53 publications
3
40
0
1
Order By: Relevance
“…These results suggest that the collaborative stance of the assessor, along with the other core values of TA, likely elicited the clients’ positive responses. This interpretation of the results is augmented by empirical studies concerning the assessor-client relationship, which is fostered by the structure and techniques of the TA model (e.g., De Saeger et al, 2014; Hilsenroth et al, 2004). Further, client reports of experiencing positive accurate mirroring, indicating that the assessor made the client feel understood and validated, reflect a key component of the theory of change in TA: During the summary and discussion of findings, clients are first presented with information that is congruent with their self-view; in other words, they experience positive accurate mirroring.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These results suggest that the collaborative stance of the assessor, along with the other core values of TA, likely elicited the clients’ positive responses. This interpretation of the results is augmented by empirical studies concerning the assessor-client relationship, which is fostered by the structure and techniques of the TA model (e.g., De Saeger et al, 2014; Hilsenroth et al, 2004). Further, client reports of experiencing positive accurate mirroring, indicating that the assessor made the client feel understood and validated, reflect a key component of the theory of change in TA: During the summary and discussion of findings, clients are first presented with information that is congruent with their self-view; in other words, they experience positive accurate mirroring.…”
Section: Discussionmentioning
confidence: 98%
“…In multiple studies comparing TA to traditional assessment (e.g., Ackerman et al, 2000; Hilsenroth et al, 2004) or other brief intervention (De Saeger et al, 2014), clients in the TA condition reported acceptability or satisfaction as high or higher than the comparison condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations